1980
DOI: 10.1149/1.2130069
|View full text |Cite
|
Sign up to set email alerts
|

On the Oxidation Kinetics of Silicon: The Role of Water

Abstract: The theory of the kinetics of the thermal oxidation of silicon is extended after critical examination of the solubility and transport behavior of water in silica. From the solubility data for water in silica reported in the literature, the dissolution appears to be a two‐stage process at temperatures up to 1200°C. In the first stage silanol groups are formed at a relatively slow rate. In the second stage these silanol groups react with water forming hydronium ions false(H3O+false) and silicate ions false(=S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…varies linearly with distance x from the interface Si/SiO,, that the silanol is in equilibrium with these species, and therefore that the concentration of silanol in the film will vary as (1 -X / X ) ' '~, where X is the thickness of the film and x the distance from the Si surface (Breed and Doremus '1976). Wolters (1980), however, examining the data of Burkhardt, comes to the conclusion that the silanol concentration is observed to vary as (1 -x / X ) * '~ and deduces that the oxidizing agent is not H,O but the ion pair H 3 0 + and OH-. The argument in terms of detailed balancing is as follows.…”
Section: $5 Profile Of Hydroxyl Groups In Sio Formed In Water Vapourmentioning
confidence: 99%
“…varies linearly with distance x from the interface Si/SiO,, that the silanol is in equilibrium with these species, and therefore that the concentration of silanol in the film will vary as (1 -X / X ) ' '~, where X is the thickness of the film and x the distance from the Si surface (Breed and Doremus '1976). Wolters (1980), however, examining the data of Burkhardt, comes to the conclusion that the silanol concentration is observed to vary as (1 -x / X ) * '~ and deduces that the oxidizing agent is not H,O but the ion pair H 3 0 + and OH-. The argument in terms of detailed balancing is as follows.…”
Section: $5 Profile Of Hydroxyl Groups In Sio Formed In Water Vapourmentioning
confidence: 99%
“…[26,27] Wolters, for example, who analyzed interactions of O 2 ─H 2 O mixtures with silica, proposed that solubility of water proceeds in two steps at temperatures up to 1100 C: 1) the slow formation of SiOH groups (the mobility of which can be neglected) and 2) the fast hydrolyzation and the formation of H 3 O þ and SiOH À . [27] Finally, it was shown that water migrates through silica by H 3 O þ and OH À . [27] It was, thus, concluded that water may play a significant role in the oxidation rate even at a dilute level.…”
Section: Resultsmentioning
confidence: 99%
“…Such a law underestimates the oxide thickness when the linear-parabolic regime is reached, and hence, the mechanism responsible for the oxygen diffusion enhancement in thicker oxides should be found. One plausible mechanism has already been proposed by Wolters et al [45,46], who considered a water-enhanced oxygen diffusion in the thick-oxide growth regime, but other mechanisms should also be tested. However, since the presentation of an oxidation model is out of the scope of this paper, we will consider that the SiO, growth is described by a purely parabolic law, t = Ad2 in the initial oxidation regime, and we will smoothly link this law to a linear-parabolic one that has been found to be valid for the rest of the oxidation process.…”
Section: Silicon Thermal Oxidation: Local Versus Average Sioz Growthmentioning
confidence: 98%